If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7+7(x+3)=7
We move all terms to the left:
-7+7(x+3)-(7)=0
We add all the numbers together, and all the variables
7(x+3)-14=0
We multiply parentheses
7x+21-14=0
We add all the numbers together, and all the variables
7x+7=0
We move all terms containing x to the left, all other terms to the right
7x=-7
x=-7/7
x=-1
| 5m+2(m-5)=-66 | | 5xx11=120 | | 8(x+1)-4x-6=2(x+1) | | 30=-3(x-4) | | 6(y+9)-12=0 | | 1/12x+7=2 | | 2x^+x=3 | | 8+5(a-4)=18 | | 5x+1/3-4=5-7x | | x–4=-8. | | (128-x)=x | | -20=a/19 | | 1/2(4x+12)=2-x+1 | | 15m+5=5m+15 | | 0.04-0.44=0.02x | | 6x^-36=0 | | 6b+3=3b+6 | | (x-5)22=90 | | X+(.17*x)=50 | | 6x+10=189 | | 75x=5000 | | 5x+6=5(x+1)+1 | | 4/3(3.14)(3)^2=x | | -2(2m+4)=3(2+m) | | -1/5x+2/25=0 | | X+.17(x)=50 | | 5x-25/2=0 | | 3x+11=-2x-5 | | 7x=37.35 | | 5n=n4 | | 12+((2/3)12-3)=x | | 2x+2x=13-1 |